(untitled) (Global Journal of Management and Business Research, 2018)
The study is based on finding out the impact of credit risk management on the performance of commercial banks with specific objectives of evaluating loan assessment techniques used by banks and finding out various risk management tools used to manage credit risk. In order to verify it, secondary data were used to carry out ratio analyses and trend analyses which were then correlated to the percentages changes in profits. The findings of the study indicated that the Non- Performing loans (NPL) to total loans ratio which is one of the risk management indicators is a major predicator and is significantly related to bank financial performance, followed by the loan to total deposit ratio and loans to total assets ratios that have an inverse impact on financial performance of banks.